Hipoxia Neonatal y su efecto en el desarrollo Psicomotor en niños menores de 2 años atendidos en el Hospital Minsa II-2 Tarapoto, periodo Noviembre 2015 – Marzo 2016 - Delgado García, Valeria Milagros (2016)
The following research aimed to determine the effect of the neonatal hypoxia in psychomotor development in children less than two years attended in the Ministry of Health II-2 Tarapoto Hospital from November 2015 to March 2016. The study was quantitative, descriptive, retrospective, and prospective with correlational design. The sample was represented by 30 term infants with hypoxia. The measure instrument, Peruvian Assessment Test Development of Children was used, taken from the health standards for growth controlling and development of child and children under 5 years. The results were: 76.7% (23) of mother’s ranges from 20 to 34 years of age, 16.7% (5) are from Shilcayo district 90.0% degree of secondary education and 70.0% completed the cesarean delivery. 30.0% of the children made marked neonatal hypoxia, evaluated through APGAR test at the minute of birth and 100% moderate at 5 minutes (4-6 points). 100.0% of children in the study found that 66.7% had normal psychomotor development, developmental disorder 20.0%, 10.0% risk for developmental disorder and 3.3% advance development. Conclusions: The effect of the neonatal hypoxia in psychomotor development in children under 2 years is statistically significant (p <0.05)